MANAJEMEN USAHA IKAN CAKALANG ASAP DI KELURAHAN GIRIAN BAWAH KECAMATAN GIRIAN KOTA BITUNG PROVINSI SULAWESI UTARA - Kairupan, Dewinta; Jusuf, Nurdin; Londong, Florence V. (Universitas Sam Ratulangi, 2014)
Abstract Bitung city consists of 8 sub-districts and 69 villages, Girian Bawah Satu village under some people have a job that is entrepreneurship. Business activities are producing smoked tuna; these efforts are made to develop the processing of fish that meets the needs of the family, and create additional jobs for the local community. This study aims to determine the business management of tuna smoked, knowing the marketing chain, workforce and how the remuneration, and analyzing the feasibility of smoked tuna. Data collection techniques used in this study is the Census is a business owner smoked tuna in the Girian Bawah village totaled 10 business owners. Results showed generally smoked tuna business in the Lower Girian Bawah village still in the stage of